Studi Kasus Pola Asuh Anak Jalanan yang Memiliki Keluarga Broken Home - Endang Dewi Galih Nur Rima; Sri Weni Utami; Indah Yasminum Suhanti (Fakultas Psikologi Universitas Negeri Malang, 2020)
Parenting in homeless families in which the parents come from broken home is authoritarian type. However, this can not be generalized to all homeless. Type of parenting homeless, whose parents got divorce influenced by past trauma. In research conducted in the sub-district Sukun and Belimbing in 4 men and women (20–30 years). The research method is case study. Analyzed data using thematic data. Results indicate parenting pattern of subjects A and D are ambiguous type. It is because they let their children do whatever they want to and fulfill to their needs, but still give punishment to them when they deserve it. Parenting pattern of subjects B and C are permissive type. This is because they let children do whatever they want to and fulfill to their needs without giving any punishment.